STUDI KARAKTERISTIK TANAH PADA LAHAN TANAMAN JAGUNG HIBRIDA PIONEER 23 DI KECAMATAN TIGO NAGARI KABUPATEN PASAMAN - Fitriani, Riza - (STKIP PGRI Sumbar, 2014)
This research was conducted to know and to analyze the characteristics of the soil(structure, texture, pH andorganic matter) hybrid maize pioneer 23 land at Tigo Nagarisub districtof Pasaman district.This research method is descriptive. Map of land units used as the basis ofsampling research. Land units obtained from the overlay of landforms, slope, map soiltype, land use, andgeological maps. Soil sampling conducted by purposive samplingtechnique.The results showed that: 1.The soil structure on land units are crumb and blocky.2.The soil texture on land units are texture loam and dusty clay. 3. The pH of the soil, onland units have excellent category. 4. Organic material in the sample categorized landunits are excellent and good categories. Then the soil characteristics on hybrid maizepioneer 23 land atTigo Nagari sub district of Pasaman district. Categorized into twogood and fair. Both categorieson land units V2.IV.Alv.Sw.Qat (sample I) and land unitsV4.II.Alv.Pm.Qat (sample II). While beingin the category of land units F1.I.Alv.TL.Tmv(sample III)